Genetic variation in growth traits and yield of rubber trees (Hevea brasiliensis) growing in the Brazilian state of São Paulo - de Souza Gonçalves, Paulo; de Moraes, Mário Luiz Teixeira [UNESP]; Bortoletto, Nelson; da Costa, Reginaldo Brito; Gonçalves, Elaine Cristine Pifer (FapUNIFESP (SciELO), 2005)
Analysis of variance and covariance was preformed on growth traits (stem girth, bark thickness, total height gain and rubber yield) of 22 open-pollinated progenies of the rubber tree Hevea brasiliensis from an Asian Hevea collection introduced to Agronomic Institute (Instituto Agronômico, Campinas, São Paulo, Brazil; IAC) in 1952. This progeny trial was replicated at three sites in São Paulo state and it was found that at three years from sowing there was statistically significant variation for girth, bark thickness, height and rubber yield. An individual test sites, values of individual plant heritability for girth ranged from ĥ i 2 = 0.36 to ĥ i 2 = 0.89 whereas values for heritability for progeny means ranged from ĥ i 2 = 0.77 to ĥ i 2 = 0.87. These moderate and high heritabilities suggest that a combination of progeny and within-progeny selection would be effective at increasing girth in this population at individual sites. Across sites, values of individual-plant heritability for girth ranged from ĥ i 2 = 0.36 to ĥ i 2 = 0.47, whereas values for heritability of progeny means girth ranged from ĥ x̄ 2 = 0.77 to ĥ x̄ 2 = 0.87. There were high positive genetic correlations between increased girth and bark thickness suggesting that breeding aimed at increasing girth would also increase bark thickness and possibly height. Copyright by the Brazilian Society of Genetics.
Keywords: Genetic parameters; Heritability; Hevea brasiliensis; Rubber tree; rubber; analysis of covariance; analysis of variance; bark; Brazil; controlled study; genetic correlation; genetic selection; genetic trait; genetic variability; heritability; nonhuman; plant breeding; plant genetics; plant growth; plant height; plant yield; pollination; progeny; sowing; statistical significance; tree trunk; Hevea